Analysis of Coal Briquette Quality Control at PT. Asririmba Wirabhakti - Sabatiyah, Nur; Abdillah, Willy (Universitas Bengkulu, 2024)
The aim of this research is to determine the level of quality of coal briquette production, to analyze the types of damage that occur to the products produced and to identify what factors cause damage to products produced by PT. Asririmba Wirabhakti. The sample used in this research was PT. Asririmba Wirabhakti. This research uses the statistical quality control (SQC) analysis test method. The results of this study indicate that from January to June 2023 it can be concluded that the damaged product in the coal briquettes produced by PT. Asririmba Wirabhakti did not earn more than 10% during that period. This shows that the performance of the production team at PT. Asririmba Wirabhakti is doing quite well, with a defective product rate of no more than 10% per month. Based on the image of the control chart above, it can be seen that the data obtained were 2 (two) points which were outside the control limits and 4 (four) points which were within the control limits, so that it can be said that the process is under control. This states that quality control at PT. Asririmba Wirabhakti is good enough. Because the points that experience deviations (2 points) are fewer than the points that do not experience deviations (4 points). From the analysis of the causal diagram, it can be seen that the factors that cause damage or defects in production come from human/worker factors, production machines, work methods, materials/raw materials.